The Traditional Religion of the Dayak in West Kalimantan: Analysis of J.U. Lontaan’s Monograph - Taggok, M. Ikhsan; Hawari, Muhammad Rifqi (Center for Research and Development of Religious Literature and Heritage, 2021)
The aim of this paper is to explain Lontaan's views on the religious beliefs of the Dayak people in West Kalimantan as set forth in his book The History of Customary Laws and Traditions of West Kalimantan. It concentrates on the concept of traditional Dayak religion in Lontaan's work, which is still developing today even though the Dayak have embraced religions foreign to their island. In understanding, examining and explaining Lontaan’s monograph, this paper uses a descriptive hermeneutical method. The source of this paper is the book The History of Customary Laws and Traditions of West Kalimantan by Lontaan. The data of this paper is Lontaan’s field observations and interviews involving religious and traditional figures in West Kalimantan, which he compiled in The History of Customary Laws and Traditions of West Kalimantan forty-five years ago. The focus of this paper is the traditional Dayak religion (Kaharingan) and concerns the beliefs in God, spirits and ancestral spirits that it comprises. Based on the results of our research, it is clear that Lontaan succeeds in showing that the Dayaks’ beliefs about spirits or gods and ancestral spirits can affect their daily lives. To connect with God, spirits and ancestral spirits, the Dayak hold various ceremonies. In contrast to other works on Dayak, Lontaan not only studied one of the Dayak tribes, but also examined the culture and religious beliefs of the Dayak Kenayatn, Kayan, Maayan and other Dayak tribes in West Kalimantan and its customs compared to each other.